Orthoptera (Insecta: Tettigonioidea, Pyrgomorphoidea, Acridoidea) of Kafa Biosphere Reserve, Bale Mountains National Park and other areas of conservation interest in Ethiopia - Felix, Rob P.w.h.; Massa, Bruno (Zootaxa, 2016)
An annotated checklist of 51 Orthoptera taxa (Tettigonioidea, Pyrgomorphoidea and Acridoidea) of Kafa Biosphere Reserve, Bale Mountains National Park and some additional sites in Ethiopia is presented. Ten species are newly recorded for the country. Four species are new to science: Peropyrrhicia attilioi n. sp., P. keffensis n. sp., P. semiensis n. sp. and Coryphosima danieli n. sp. The status of Peropyrrhicia cooperi Uvarov, 1934 and P. scotti Uvarov, 1934 is revised: both are considered valid species.